Efektivitas Multimedia Berbasis Problem Based Learning terhadap Hasil Belajar IPAS Siswa Sekolah Dasar - Muhammad Bayu Pamungkas (Lembaga Yasin AlSys, 2026)
Natural and Social Sciences (IPAS) learning in elementary schools plays an important role in developing students’ scientific, logical, and critical thinking skills. However, IPAS learning is still dominated by conventional methods and the limited use of instructional media, resulting in low student learning outcomes, particularly for abstract topics such as the water cycle. This study aims to analyze the effectiveness of Problem-Based Learning (PBL)-based multimedia in improving elementary school students’ IPAS learning outcomes. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 20 fifth-grade students at SDN Jarakan 2. Data were collected through learning outcome tests in the form of pretests and posttests, validation sheets completed by media and subject-matter experts, and student response questionnaires. The data were analyzed using quantitative and qualitative descriptive methods. The results showed that the students’ mean score increased from 52.5 on the pretest to 81 on the posttest, with an N-gain score of 0.60 in the moderate category. Classical learning mastery also increased from 25% to 85%. Expert validation results indicated that the multimedia was categorized as highly feasible, while student responses were categorized as very good. These findings demonstrate that PBL-based multimedia is effective in improving IPAS learning outcomes and supporting the creation of more meaningful, contextual, and student-centered learning. This study provides practical implications for teachers in developing and utilizing problem-based multimedia to improve the quality of IPAS learning in elementary schools.